The performance of deterministic and stochastic interest rate risk measures: another question of dimensions? - Oliveira, L. (2015)
The efficiency of traditional and stochastic interest rate risk measures is compared under one-, two-, and three-factor no-arbitrage Gauss-Markov term structure models, and for different immunization periods. The empirical analysis, run on the German Treasury bond market from January 2000 to December 2010, suggests that: i) Stochastic interest rate risk measures provide better portfolio immunization than the Fisher-Weil duration; and ii) The superiority of the stochastic risk measures is more evident for multi-factor models and for longer investment horizons. These findings are supported by a first-order stochastic dominance analysis, and are robust against yield curve estimation errors.